Consumer Brand Relationships - Ghani, Noor Hasmini Binti Abd; Tuhin, Mohammad Kashedul Wahab (International Review of Management and Marketing, 2016)
We have investigated the dynamics of how consumer make relationship with brand (non-human entities) that is consumer brand relationships. This relationship is like the same relationship between two people in the society. Meta-analytic literature review has been conducted to explore different aspect of this relationship dynamics. The investigation reveals that brands work as a relationship partners with consumers. Relationship dimensions, which are considered as ground of relationship types, constructed by authors differs resulting different types consumer brand relationships. However, various authors measure relationship quality based on the same ground relationship strength and feelings using different theories. This research has implications for both academicians and practitioners as they can comprehensively conceptualize the consumer brand relationship, its nature, type and dimensions explored by researchers and their present state. Keywords: Consumer Brand Relationship, Relationship Dimensions, Relationship Types. JEL Classifications: M30, M31